A Case Study Analysis of System Efficiency, Viability and Energy Values of SOFC Based Fuel Cell Micro-CHP for Office Buildings. (2nd June 2015) - Tesfai, Alem Teklebrhan; Mylona, Anastasia; Connor, Paul; Cassidy, Mark; Irvine, John T. S.
Abstract : The built environment is a large contributor to the greenhouse gas emissions. The first step in tackling environmental impact and fuel cost reduction is the minimization of energy losses through introduction of new and more efficient energy conversion technologies. In this study, the potential application of fuel cell micro-CHP in a typical office building is investigated. A 1.5 k Welfuel cell micro-CHP has been installed in an office building at CIBSE headquarters (HQ). The unit converts natural gas to electricity, using Solid Oxide Fuel Cell (SOFC) stack. The installation and data from the operation of the system is discussed. The data shows that the heat recovered from the SOFC stack covers most of the domestic hot water requirement of the office building, requiring minimal top-up from the immersion heater.